2008
DOI: 10.1136/jnnp.2007.125385
|View full text |Cite
|
Sign up to set email alerts
|

The use of EEG in the diagnosis of dementia with Lewy bodies

Abstract: Although reports on EEG in dementia with Lewy bodies (DLB) are conflicting, the recent diagnostic guidelines define EEG abnormalities as being supportive for the diagnosis. We examined EEG abnormalities in 18 patients with DLB, 34 patients with Alzheimer's disease (AD) and 36 patients with subjective memory complaints (SMC) using the Grand Total EEG (GTE) score. There was a difference in median GTE score of DLB (11.0), AD (4.8) and SMC (2.5) (p<0.001). Patients with DLB had higher scores than patients with AD.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
56
2
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(64 citation statements)
references
References 24 publications
4
56
2
1
Order By: Relevance
“…The more frequent demonstration of both focal and diffuse EEG abnormalities in DLB and VaD compared to AD is in agreement with previous studies [12,14,18,19] , although 1 study found focal abnormalities not sufficiently prevalent to distinguish VaD from AD [13] . Two studies failed to distinguish DLB from AD by visually scoring predominantly diffuse EEG disturbances on a 4-point scale [15,16] , which is probably less sensitive than the visual interpretation of an EEG pattern, which includes the scoring of both diffuse and focal abnormalities.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The more frequent demonstration of both focal and diffuse EEG abnormalities in DLB and VaD compared to AD is in agreement with previous studies [12,14,18,19] , although 1 study found focal abnormalities not sufficiently prevalent to distinguish VaD from AD [13] . Two studies failed to distinguish DLB from AD by visually scoring predominantly diffuse EEG disturbances on a 4-point scale [15,16] , which is probably less sensitive than the visual interpretation of an EEG pattern, which includes the scoring of both diffuse and focal abnormalities.…”
Section: Discussionsupporting
confidence: 92%
“…Three cohort studies of DLB patients (n = 10-18) did not include 1 patient with a visually rated normal EEG [14,17,18] , which support our findings. The prevalence of a normal EEG in VaD has previously been reported to be either the same or lower than in AD [12,13] .…”
Section: Discussionsupporting
confidence: 76%
“…It is also of great importance to verify whether EEG helps to distinguish between AD and other dementias; in the last years, studies have investigated whether EEG alone allows to differentiate between AD, subjective memory complaints [116,173,175], psychiatric disorders [173], vascular dementia [173,176,177,178,179,180], fronto-temporal dementia [116,173,180], dementia with Lewy bodies [173,181,182], dementia with Parkinson's disease [182], and vascular dementia with Alzheimer's disease [60]. The preliminary results are generally promising, but surely, additional investigations will be required to explore the potential of EEG for differential diagnosis of dementia, and brain disorders at large.…”
Section: Differential Diagnosis Of Dementiamentioning
confidence: 99%
“…Roks és mtsai DLB-ben lassabb hát-téraktivitást, diffúzabb lassúhullám-tevékenységet, csök-kent reaktivitást és magasabb proximális aktivitást detektáltak az AD-hez képest. Feltételezik, hogy a kifejezettebb EEG-változások hátterében a súlyosabb kolinergdeficit állhat [60].…”
Section: Elektroencefalográfia (Eeg) éS Liquor-biomarkerekunclassified